2010
DOI: 10.1103/physrevb.82.014501
|View full text |Cite
|
Sign up to set email alerts
|

Scanning SQUID microscope study of vortex polygons and shells in weak-pinning disks of an amorphous superconducting film

Abstract: Direct observation of vortices by the scanning SQUID microscopy was made on large mesoscopic disks of an amorphous MoGe thin film. Owing to the weak pinning nature of the amorphous film, vortices are able to form geometry induced, (quasi-)symmetric configurations of polygons and concentric shells in the large disks. Systematic measurements made on selected disks allow us to trace not only how the vortex pattern evolves with magnetic field, but also how the vortex polygons change in size and rotate with respect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 29 publications
3
53
2
Order By: Relevance
“…5, we observed a one dimensional vortex distribution on an annulus, and found that the vortex spacing (a) did not follow the Abrikosov lattice derived from the GL equation, 2 √3 ⁄ / for a close-packed hexagonal array; this equation leads to sparse vortices at low fields (H < 0.7 T) and dense vortices at high fields (H > 0.7 T). In previous measurements of mesoscopic superconducting disks [4,16,45], the first vortex is typically observed in the center of the disk in contrast to the results in Fig. 5.…”
Section: Islandscontrasting
confidence: 53%
“…5, we observed a one dimensional vortex distribution on an annulus, and found that the vortex spacing (a) did not follow the Abrikosov lattice derived from the GL equation, 2 √3 ⁄ / for a close-packed hexagonal array; this equation leads to sparse vortices at low fields (H < 0.7 T) and dense vortices at high fields (H > 0.7 T). In previous measurements of mesoscopic superconducting disks [4,16,45], the first vortex is typically observed in the center of the disk in contrast to the results in Fig. 5.…”
Section: Islandscontrasting
confidence: 53%
“…Moreover, a different approach is needed to explore the condensate in the nondissipative (zero voltage) state. In order to tackle these issues a second set of experiments probes the magnetic field profiles, generated by the superconducting currents, by using magnetic field sensitive probes (e.g., Hall probe [7,8], scanning Hall probe microscopy [9], Bitter decoration [10], and scanning SQUID microscopy [11]). These techniques indeed visualized the symmetry-induced vortex configurations in superconducting nanostructures within the low confinement regime (i.e., nanostructure size ∼λ ξ ).…”
mentioning
confidence: 99%
“…In this study, we extend the previous work not only to study vortex states in equilateral triangle dots for L more than 11 (up to 15), but also to understand whether vortex arrangements can be interpreted in terms of vortex shells, as seen in circle and square dots [7,12].…”
Section: Introductionmentioning
confidence: 54%
“…The sample stage has three stepper motors which allow us to approach and scan the samples in scales of µm with respect to the magnetic sensor. The vortex images presented in this study were taken on equilibrium vortex states prepared by the field-cool procedure, in which the magnetic field was applied in some temperatures (∼ 15 K) above T c , followed by cooling the samples in the magnetic field to temperatures of 3-4 K (< T c ) for imaging [7]. 3,12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation